2018
DOI: 10.1002/slct.201703131
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Controlled Nanoparticles Formation and Tracking of Lysosomal Zinc Ions in Cancer Cells by Fluorescent Carbazole–Bipyridine Conjugates

Abstract: Fluorescent probes for simultaneous detection of multiple organelle specific analytes in cancer cells are essential for bioimaging applications. During abnormalities in cells, among other important parameters (metal ions, reactive oxygen species (ROS), enzymes, etc.) pH and Zn2+ are also altered in cells. Herein, we report the formation of nanoparticles of the fluorescent molecules based on carbazole‐bipyridine conjugates (CBL1‐3) and their use as nanoprobes to simultaneously detect Zn2+ and pH variations in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Following iron, the transition metal ion Zn 2+ is the second most abundant metal ion in the human body. It plays a vital role in regulating immune function, signal transduction, and the operation of metalloenzymes . In healthy individuals, the concentration of Zn 2+ in serum typically falls within the range of 1–10 μM.…”
Section: Lysosomal Metal Ion Detectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Following iron, the transition metal ion Zn 2+ is the second most abundant metal ion in the human body. It plays a vital role in regulating immune function, signal transduction, and the operation of metalloenzymes . In healthy individuals, the concentration of Zn 2+ in serum typically falls within the range of 1–10 μM.…”
Section: Lysosomal Metal Ion Detectionmentioning
confidence: 99%
“…Recently, Ajayaghosh and co-workers reported the synthesis of a series of self-assembled fluorescent nanoprobes based on carbazole-bipyridine derivatives CBL1–3 and CBG ( 14 ), as shown in Figure a . The authors found that compared to the monomers of CBL1 and CBL3, the CBL2 nanoprobes exhibit promising results in the simultaneous detection of Zn 2+ and pH variations in lysosomes.…”
Section: Lysosomal Metal Ion Detectionmentioning
confidence: 99%
See 3 more Smart Citations